DESIGN AND DESIGN OF A REAL-TIME KWH ELECTRICITY MONITORING SYSTEM BASED ON INTERNET OF THINGS IN SOLAR POWER PLANT - Hadiyanto Hadiyanto; Syahruddin Syahruddin; Ali Abrar (Universitas Mulia, 2023)
Monitoring electrical energy in the residential sector is necessary because the current use of electrical energy is less effective and is used very excessively and consumes more electrical power. So far, electrical power usage can only be seen through a kWh meter and only shows the cumulative amount of electrical energy used. However, the design limitations of analog panels only display aggregate consumption data, not real-time consumption data and allow direct monitoring in the field as well as manual recording, so more power is required and the process takes a long time. This research aims to design a real-time measurement system that is capable of monitoring electrical energy parameters for buildings in the residential sector for solar cell-based plants, so that consumers can monitor electricity consumption in real time via the internet. The research methodology is an experiment carried out using the monitoring system design method. Through a research scheme, collaboration with industry is proposed for 1 year with the first stage being hardware design, second being software programming. Hardware and software are connected so that the information presented can be accessed directly at that time. This device is designed to replace manual and conventional electrical energy measurement systems. The research results that will be obtained are a design for a real-time electrical power consumption monitoring system in the housing sector. The output is information on electrical energy consumption through off-line and on-line application media which is displayed on a desktop application on a computer, where the data delivery system is via communication